Effect of the sulfur and fluorine concentration on physical properties of CdS films grown by chemical bath deposition - K.E. Nieto-Zepeda; A. Guillén-Cervantes; K. Rodríguez-Rosales; J. Santos-Cruz; D. Santos-Cruz; M. de la L. Olvera; O. Zelaya-Ángel; J. Santoyo-Salazar; L.A. Hernández-Hernández; G. Contreras-Puente; F. de Moure-Flores (Results in Physics, 2017)
Undoped and F-doped CdS thin films were grown on glass slides by chemical bath deposition using thiourea, cadmium acetate and ammonium fluoride as sulfur, cadmium, and fluorine sources, respectively. Undoped CdS films were deposited varying the concentration of thiourea. Once the optimal thiourea concentration was determined, based on the crystalline quality of the samples, this concentration was maintained and ammonium fluoride was added at different concentrations in order to explore the effect of the F nominal concentration on properties of CdS films. Undoped and F-doped CdS films were characterized by X-ray diffraction, UV–Vis, room temperature photoluminescence, and four probe resistivity measurements. Results showed highly transparent F-doped CdS films with strong PL and low resistivity were obtained. Keywords: CdS films, F-doped CdS films, Chemical bath deposition, Optical properties, Room temperature photoluminescence